Healthcare Costs and Resource Use of Patients with Dupuytren Contracture Treated with Collagenase Clostridium Histolyticum or Fasciectomy: A Propensity Matching Analysis [Corrigendum] - Zah V; Pelivanovic J; Tatovic S; Vukicevic D; Imro M; Ruby J; Hurley D (Dove Medical Press, 2021)
Zah V, Pelivanovic J, Tatovic S, et al. Clinicoecon Outcomes Res. 2020;12:635–643. The authors have advised that the Disclosure statement on page 642 is incorrect. The first sentence “Vladimir Zah, Djurdja Vukicevic, and Martina Imro are employees of ZRx Outcomes Research Inc. (institution founded by Endo Pharmaceuticals to conduct the present analysis), and have received grants from Endo Pharmaceuticals Inc” should read “Vladimir Zah, Djurdja Vukicevic, and Martina Imro are employees of ZRx Outcomes Research Inc. (institution funded by Endo Pharmaceuticals to conduct the present analysis), and have received grants from Endo Pharmaceuticals Inc”. The authors apologize for this error. Read the original article